2008
DOI: 10.1017/s0950268808000940
|View full text |Cite
|
Sign up to set email alerts
|

Hantavirus disease (nephropathia epidemica) in Belgium: effects of tree seed production and climate

Abstract: Recently, human cases of nephropathia epidemica (NE) due to Puumala virus infection in Europe have increased. Following the hypothesis that high reservoir host abundance induces higher transmission rates to humans, explanations for this altered epidemiology must be sought in factors that cause bank vole (Myodes glareolus) abundance peaks. In Western Europe, these abundance peaks are often related to high tree seed production, which is supposedly triggered by specific weather conditions. We evaluated the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
170
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(180 citation statements)
references
References 35 publications
7
170
2
1
Order By: Relevance
“…Thus, local climate (e.g., temperature and humidity) was more likely to directly affect life cycle dynamics (e.g., reproductive rates and incubation periods) of the disease agents themselves, whereas largerscale factors (e.g., SOI) could also influence broader ecologic processes and have possibly nonlinear impacts on disease transmission dynamics. 18,46,47 A clear association between rainfall and HFRS was not detected in this study. The association between HFRS epidemics and rainfall is still a matter of debate.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Thus, local climate (e.g., temperature and humidity) was more likely to directly affect life cycle dynamics (e.g., reproductive rates and incubation periods) of the disease agents themselves, whereas largerscale factors (e.g., SOI) could also influence broader ecologic processes and have possibly nonlinear impacts on disease transmission dynamics. 18,46,47 A clear association between rainfall and HFRS was not detected in this study. The association between HFRS epidemics and rainfall is still a matter of debate.…”
Section: Discussioncontrasting
confidence: 59%
“…However, other studies in Scandinavia have shown that warm winters led to a decrease in vole populations as a result of the decrease in protective snow cover. 18,19 Moreover, studies in eastern China showed that excessive precipitation could have a negative impact on rodents by destroying their habitats. 8,20 In addition, temperature, vegetation type, land use, and ENSO have been shown to be associated with the transmission of HFRS in China.…”
Section: Introductionmentioning
confidence: 99%
“…"New episodes of plague outbreaks" are defined as plague outbreaks that were not preceded by other recorded plague outbreaks in those regions in the 2 y before. This selection procedure resulted in a shortlist of 16 Table S2). This list is likely incomplete, because we can epidemiologically only detect harbor reintroductions of plague when there are no plague outbreaks still circulating nearby from a previous introduction of the disease.…”
Section: Significancementioning
confidence: 99%
“…Its climate is more humid than the climates of most modern plague foci (7), and its putative medieval plague reservoirs need not necessarily have responded to climate fluctuations in the same way as the modern plague foci. Nevertheless, rodent disease reservoirs in Europe, such as hantavirus in bank voles (16), are responsive to climate fluctuations in comparable ways to plague foci, with outbreaks following periods of warm and/or wet conditions that are favorable for vegetation growth, and thus for increases in rodent population density (reviewed in ref. 17).…”
mentioning
confidence: 99%
“…Moreover, "late winter NE peaks" subsequent to heavy autumn masting may ensue the following year, hereby announcing already very early an important NE peak that same year: the record number of 22 Belgian NE cases in February 2005 was heralding the most important summer NE peak ever recorded in Belgium, and an even higher February 2008 record with 28 cases announced the second highest (336 cases) peak that same year . A recent similar study, relying on the same Belgian 1995-2007 NE registry, came independently to exactly the same conclusions: NE outbreaks are favoured by hot summers two years before, and warm autumns one year before the facts (Tersago et al, 2009). …”
Section: The Belgian Studymentioning
confidence: 57%